Effect of ZnO Seed Layer on the Growth of ZnO Nanorods on Silicon Substrate. (2019) - Toe, M.Z.; Jusoh, N.A.H.N.; Pung, S.Y.; Yaacob, K.A.; Matsuda, A.; Tan, W.K.; Han, S.S.
Abstract: Highly vertically aligned ZnO nanorods (NRs) are preferred for the fabrication of devices such as solar cells, integrated circuits and light emitting diodes. However, ZnO NRs are randomly grown on silicon (Si) (100) substrate attributed to a large lattice mismatch (∼40 %) between Si and ZnO. The alignment of ZnO NRs could be improved by pre-deposition of a highly (002) oriented ZnO seed layer on the of surface Si substrate. In this work, ZnO seed layer was pre-deposited onto the Si substract by spin coating and followed by annealing. Parameters such as rotation speed, number cycles of spin coating and annealing temperatures were systematically studied. The results showed that 1000 rpm spin coating rate with the 11 spin cycles produced the most uniform coverage of ZnO NRs on Si with annealing temperature of 350°C. Micrographs of the samples show that the ZnO NRs are well-aligned with average diameters of ∼ 23 nm. In addition, the XRD analysis indicated highly aligned ZnO NRs were grown in [0001], i.e. perpendicular to (002) of the ZnO seed layer.